How would you balance the following equation: Fe+O2 --> Fe2O3?

1 Answer
Nov 2, 2015

4Fe + 3O2 2Fe2O3

Explanation:

Step 1: Tally the number of atoms based on subscript.

Fe + O2 Fe2O3 (unbalanced)

left side: Fe = 1; O = 2
right side: Fe = 2; O = 3

Step 2: Start balancing the simple molecules first, in this case the O2

Fe + 3O2 Fe2O3

left side: Fe = 1; O = 2 x 3 = 6
right side: Fe = 2; O = 3

Since there are now 6 O atoms on the left, there must also be 6 O atoms on the right. Notice that the right hand is one big molecule so whatever coefficient you would use to balance the O atoms, you would also need to apply to the bonded Fe atom.

Fe + 3O2 2Fe2O3

left side: Fe = 1; O = 2 x 3 = 6
right side: Fe = 2 x 2 = 4; O = 3 x 2 = 6

Step 3: Now balance the rest of the equation.

4Fe + 3O2 2Fe2O3

left side: Fe = 1 x 4 = 4; O = 2 x 3 = 6
right side: Fe = 2 x 2 = 4; O = 3 x 2 = 6

The equation is now balanced.